TEACHING HANDWASHING SOAP SKILL THROUGH DEMONSTRATION FOR KINDERGARTEN CHILDREN - Rachmawaty M. Noer; Nurlince Siregar; Mira Agusthia (International Journal of Social Science, 2021)
The research aims to find out whether Effect of Health Education Demonstration Media on Knowledge of Handwashing with Soap (CTPS) in the Work Area of ​​the Sei Pancur Health Center Batam City. Research methods used a quasi-experimental one-group pre-test-post-test. Research result shows that In the pre-test as many as 88.9% of respondents lack knowledge on washing Hands with Soap (CTPS) and on the Post-test as many as 92.6% of respondents Good knowledge of washing Hands with Soap (CTPS) in this case, there is a significant effect between the knowledge of 6 steps of handwashing before and after the intervention of health education about Hand Washing with Soap 6 Steps with demonstration media in Early Childhood in the Work Area of ​​the Sei Pancur Health Center Batam City. Conclusion: There is an effect Demonstration Method on increasing the knowledge of early childhood in proper hand washing in the Work Area of ​​the Sei Pancur Health Center Batam City. Suggestion: The school should further improve the provision of health information, especially about proper handwashing through various health education methods so that early childhood children are happy and not bored in following it.